Self-Efficacy and Interpersonal Communication Skills in College Students - Azkia, Zulfa Azka; Purnami, Sri; Muqowim, Muqowim; Athiyah, Atina Husna (JURNAL PENELITIAN PENDIDIKAN, PSIKOLOGI DAN KESEHATAN (J-P3K), 2024)
This study aims to determine the relationship between self-efficacy and interpersonal communication skills in students and to determine how accurate the self-efficacy variable is as a predictor of the interpersonal communication skills variable in students . This type of research is an ex post facto study with a correlational type. The subjects of this study were 89 PAI students from the 2022 intake. The variables in this study consist of the dependent variable, namely interpersonal communication skills and the independent variable, namely self-efficacy. The data collected is an analysis of self-efficacy and interpersonal communication skills using a questionnaire instrument. The data analysis used is simple regression analysis and product moment correlation. The results of the correlation coefficient analysis for the self-efficacy variable with interpersonal communication skills = 0.784 with a significance of 0.000 (p 0.01). The results of data analysis show a significant positive relationship between self-efficacy and interpersonal communication skills in students with a determination coefficient of 61.5% and the remaining 38.5%, and 139.140 3.95, which means there is a positive and significant relationship between self- efficacy and interpersonal communication skills in students.